2001
DOI: 10.1080/02724930020028920
|View full text |Cite
|
Sign up to set email alerts
|

A health and nutritional profile of rural school children in KwaZulu-Natal, South Africa

Abstract: A community-based cross-sectional study was undertaken to measure anthropometric indices, micronutrient status and prevalence of parasite infections in 579 rural South African primary school children. Eleven schools were selected randomly from a Magisterial District in southern KwaZulu-Natal (KZN). In each school, all pupils aged between 8 and 10 years were selected. The following outcome measures were obtained: anthropometric--height for age, weight for age and body mass index; micronutrient status--anaemia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 9 publications
1
24
0
Order By: Relevance
“…However, other studies in SA also report a higher prevalence of overweight and obesity among girls than among boys. [20,21] Significant differences were found in the overweight and obesity prevalence rates of white and black children, indicating that white learners are significantly more overweight and obese (19.7%) than *p<0.05 = significant overall and age-specific differences between black and white learners. † Significant gender differences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, other studies in SA also report a higher prevalence of overweight and obesity among girls than among boys. [20,21] Significant differences were found in the overweight and obesity prevalence rates of white and black children, indicating that white learners are significantly more overweight and obese (19.7%) than *p<0.05 = significant overall and age-specific differences between black and white learners. † Significant gender differences.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of SA studies [6,7,[20][21][22] have reported a similar prevalence for overweight and obesity among children of the same age group. The results of the National Food Consumption Survey based on the IOTF cut-off points, conducted on children between the ages of 1 and 8 years (N=2 894), showed that 6.7% of children could be classified as overweight and 3.7% as obese.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies in South Africa, northern Ethiopia, Brazil, Nepal, and Vietnam showed that the prevalence of VAD was high especially in rural areas. [6][7][8][9][10] According to the United Nations Children's Fund, Kenya, Benin, the Congo, Zambia, India, Afghanistan, and Myanmar still have a high prevalence of VAD, which can be as high as 70%. 5 Vitamin A deficiency is usually caused by prolonged dietary deprivation or inadequate intake as in Africa where hunger and malnutrition prevail.…”
Section: Introductionmentioning
confidence: 99%
“…These vitamins are important for vision, growth, and immune and neurological functions (1,2) . VA deficiency (VAD) is highly prevalent and is associated with increased occurrence of infectious diseases and mortality in several developing countries, especially in sub-Saharan Africa and South-east Asia (3)(4)(5)(6)(7)(8)(9) . In addition, improving the VA status of children in these countries can reduce morbidity and mortality (10)(11)(12) .…”
mentioning
confidence: 99%